2021
DOI: 10.3390/antibiotics10111429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imipenem and Amikacin Combination against Multi-Drug Resistant Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is an opportunistic nosocomial pathogen associated with high morbidity and mortality rates. Combination of antibiotics has been found to combat multi-drug resistant or extensively drug resistance P. aeruginosa. In this study we investigate the in vitro and in vivo effect of amikacin and imipenem combination against resistant P. aeruginosa. The checkerboard technique and time-killing curve have been performed for in vitro studies showed synergistic effect for combination. A peritonitis mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Moreover, the MIC for amikacin and nor oxacin is signi cantly reduced from 64 µg/mL to 1 µg/mL and from 256 µg/mL to 8µg/mL respectively with FIC index 0.25 as showed in table (4). This was in contact with previous studies (Farhan et al, 2021) described the synergism and the antimicrobial activity between Imipenem and amikacin in the treatment of multi drug resistant P. aeruginosa isolates.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, the MIC for amikacin and nor oxacin is signi cantly reduced from 64 µg/mL to 1 µg/mL and from 256 µg/mL to 8µg/mL respectively with FIC index 0.25 as showed in table (4). This was in contact with previous studies (Farhan et al, 2021) described the synergism and the antimicrobial activity between Imipenem and amikacin in the treatment of multi drug resistant P. aeruginosa isolates.…”
Section: Resultssupporting
confidence: 83%
“…Traditional PCR and quantitative real-time PCR practices were e ciently applied for the detection of the P. aeruginosa harbored the resistance genes bla IMP and aac(6)-Ib as well as genotyping of P. aeruginosa isolates may be grouped with multiple locus variable-number-tandem repeat analysis (MLVA) to determine the relationship and similarities between strains (Farhan et al, 2021;Schauer et al, 2021). The current study used mPCR for the detection of some virulence genes of P. aeruginosa isolates through successful ampli cation of exoT, toxA, oprL, and iasI genes at 152, 396, 504, 606 bp respectively as well as the antibiotics resistant genes for aminoglycosides and uoroquinolones antibiotics; qnrS, qnrA and aadB at 417, 516 and 319 bp respectively as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of carbapenem and amikacin has become an important treatment option to combat multidrug-resistant or extensively drug-resistant P. aeruginosa [ 13 ]. In a previous report, NDM-1–producing P. aeruginosa isolates had the highest sensitivity to tigecycline and amikacin [ 14 ].…”
mentioning
confidence: 99%
“…In addition, Farhan et al (2021) evaluated the efficacy of combining amikacin with imipenem against resistant P. aeruginosa in vitro and in vivo. They found that the combination was superior (Farhan et al, 2021). The results of this study were in opposition to their results.…”
Section: Discussionmentioning
confidence: 99%